Feedback : Tennis-ball towers. (4th June 2019) - Rogava, Andria
Abstract: As a physicist and keen tennis player, I would like to share an amusing "discovery" I recently made. In my office, I have about 20 used tennis balls and so decided to try building some tennis-ball "pyramids".